Impacted Gallstone presenting as a Cecal Tumor - Majid, Saroosh; Arif, Sabeen; Cheema, Asma Naseer; Haque, Anwar Ul (International Journal of Pathology, 2018)
describedhere is of biliary ileus in a 33years old patient. The right hemicolectomy specimen was sent for histopathologyexamination from Sheikh Khalifa Bin Zayed Hospital (SKBZH) after exploratory laparotomy. On opening, apigmented stone of mulberry type measuring 3.2x2x1.3cm was found impacted at ileocecal junction on cecal side.Microscopic examination revealed intact mucosal lining with normal morphology and distribution of colonicglands. There was fibrosis in the wall of area surrounding the stone. Mild inflammation was present in the mucosaalong with serosal congestion. Margins were healthy and no proof of carcinoid tumor or malignancy was appreciated.The case was traced retrospectively and patient was called to seek the formation of stone in this unusual place.Detailed history, examination was done and investigation reports were observed. A diagnosis of biliary ileus wasmade. It was concluded that large stone was formed as a consequence of accretion of multiple small stones droppedfrom gall bladder through a fistula. Furthermore, the small stones bound each other as a result of chemical reactioncatalyzed by the enzymes of that region.